Implementasi Manajemen Berbasis Sekolah Pada Sekolah Menengah Pertamadi Desa Tertinggal - Budi Teguh Harianto; Nelfita; Agung Wibowo (Balitbangda Provinsi Jambi, 2022)
Abstract School-based management is important for one-roof State Junior High Schools, especially those in disadvantaged areas, because it is useful in efforts to improve the quality of education. The problem faced is that the implementation of SBM is not optimal. This type of research is descriptive qualitative. Data collection was done by interview, observation, and documentation methods. The method of analysis using triangulation. Data analysis techniques include data collection, data reduction, data presentation, and drawing conclusions. The results of the study found that, (1) Leaders did not fully know about school-based management and its implementation. (2) Community participation has not been maximized in various school activities, especially to support learning activities. (3) Parents do not facilitate and provide learning assistance for students at home, especially reading activities. (4) Supervision to evaluate the implementation of school-based management in One Roof Junior High School has not been optimal. Likewise, the implementation of teacher supervision in the learning process carried out by the principal is still limited. It is recommended for further research to find tips or strategies as a solution to improve the implementation of school-based management in one-roof Junior High Schools. Stakeholders must make a program of strengthening or technical guidance for school-based management with participants from school principals, teachers and school committees. Keywords: School-Based Management, Quality of Education, One Roof Junior High School